Towards integrating rural vernacular settlements in urban regions: a study of Algarve, Portugal - Costa, Miguel Reimão (2012)
This paper deals with the vernacular settlements that often exist in the fringes of urban centres and their adaptations and absorptions within the expansions of the urban regions. In many parts of the world, the processes of urban expansions that began with the industrial revolution often led to the integration of rural settlements previously located in the outer rings of cities through adaptations that naturally took place at that time. In the recent decades however, this has become more arbitrary and in many cases have led to the loss of value of agricultural land, vernacular settlements and buildings of significant heritage values. Antagonisms have developed between the urban and rural areas and the value of vernacular settings have played little role in urban metropolitan planning. Studies of such situations can reveal how vernacular buildings and hamlets could be integrated to urban areas with appropriate development techniques. In such situations, the rural vernacular buildings and settings need to be protected; enabling them to acquire in the diffuse cities the significance that the historic centers achieved in the traditional compact cities, especially in the second half of the twentieth century. In fact, if the conventional antagonism between city and country had become less significant, the vernacular patrimony – as the ecological systems or the old rural paths and property structure – has to be considered as core considerations in urban planning. This paper argues, in this context, that one should make a distinction between the dispersion patterns and the agglomeration patterns in that they raise different questions in the land use transformations. In order to facilitate the integration of peri-urban vernacular values in metropolitan contexts, it proposes an urban development model based on heritage and landscape which assumes the relevance of appropriating the ecological and cultural structure of landscape as a basic concept of urbanization. To understand some of the issues inherent in this process, the paper looks at the lower Algarve in southern Portugal. The vernacular settlements in this area becomes important due to the fact that the present regional and municipal plans constrain the building process outside the compact urban areas to those existing rural settlements in its fringe areas.